Escape from the wasteland : romanticism and realism in the fiction of Mishima Yukio and Oe Kenzaburo - Napier, Susan Jolliffe (Harvard-Yenching Institute monograph series, 1995)
Nobel Prize winner Oe Kenzaburo and the ever-disturbing Mishima Yukio have explored twentieth-century Japanese alienation with an unsparing eye and savage humor. In Escape from the Wasteland, Susan J. Napier examines their vivid and often perverse depiction's of sex, impotence, emperor worship, and violence. For new readers of Oe and Mishima, this is an indispensable guide. For critics and scholars, it is the benchmark study.